Bathymetry Mapping and Simulation of Water Level in Cirata Reservoir Using Dual Beam Sonar - Risma Dwi Puteri Wijayanti; Najla Natasya Aurellia; Khoirotul Latifah Sobari; Kartika Hajar Kirana (Jurnal Penelitian Pendidikan IPA, 2025)
The Cirata Reservoir, an important water reservoir in West Java, plays a key role in hydropower generation, irrigation, and flood control. However, increasing sedimentation poses a significant threat to the reservoir’s functionality. This study maps the bottom topography and evaluates flood risks from sedimentation through bathymetric mapping and water level rise simulations. Data was collected from 22 sampling points using Deeper Sonar Pro+, providing precise depth measurements. Depths ranged from 2.1 m to 45.9 m, with an average of 22.4 m and a standard deviation of 13.46 m. The deepest areas are located in the center and near the Citarum River, while shallower areas are found at the estuaries of the Cibalagung and Cisokan Rivers due to sediment deposition. Simulations of water level rise using bathymetric and NASADEM data showed that a rise of up to 15 m would inundate the western, southern, and southwestern regions of the reservoir. Although the total volume of the reservoir is not determined, these findings underscore the need for effective sediment management to sustain the reservoir’s capacity and ecological functions. Further studies are required to estimate the reservoir’s volume and model long-term sedimentation risks to support the Cirata Reservoir's sustainability.